2007
DOI: 10.1080/02699050701484849
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive deterioration due to GH deficiency in patients with traumatic brain injury: A preliminary report

Abstract: Results show GH-related cognitive impairment in patients who develop GH deficiency after TBI and suggest that treatment of GH deficiency would improve cognition. The clinical importance of these findings should be established to better understand the nature, magnitude and meaning of GH-related cognitive impairment in patients who develop GH deficiency after TBI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(20 citation statements)
references
References 24 publications
1
19
0
Order By: Relevance
“…For example, Leon-Carrion et al (2007) showed a GH-related cognitive impairment in patients who develop a GH deficiency post-TBI. These patients also had deficits in memory and attention.…”
Section: Implications Of Gh=igf-1 Deficiency In Tbi Subjectsmentioning
confidence: 99%
“…For example, Leon-Carrion et al (2007) showed a GH-related cognitive impairment in patients who develop a GH deficiency post-TBI. These patients also had deficits in memory and attention.…”
Section: Implications Of Gh=igf-1 Deficiency In Tbi Subjectsmentioning
confidence: 99%
“…GH deficiency has been associated with more severe deficits in memory, attention, executive function, mood, and sleep, as well as being associated with fatigue, many of which are often reported as postconcussive symptoms. [3][4][5][6][7][8][9][10] GH also may play a critical role in recovery, as it is involved in both myelin formation [11][12][13] and neuronal plasticity. [14][15][16][17] A number of potential pathophysiological mechanisms have been suggested as to how the pituitary gland is damaged.…”
mentioning
confidence: 99%
“…Leon-Carrion demonstrated cognitive impairments in GH deficient patients after traumatic brain injury (TBI) and suggested that treatment with GH could improve cognition [8]. Preliminary results from our ongoing study assessing the effects of rhGH replacement on neuropsychological function in GH deficient adults with moderate to severe traumatic brain injury (TBI) indicate positive trends in processing speed index, memory, and integration in the community.…”
Section: Gh Replacement and Cognitionmentioning
confidence: 89%